International investment law for the 21st century essays in honour of Christoph Schreuer - Binder, Christina, 1973- (Oxford : Oxford University Press, 2009)
Leading experts from practice and academia address fundamental questions and topical problems of international investment protection in this volume, such as the future of investment law and its relation to human rights.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Investments, Foreign (International law)